Web-based Academic Information System at Darun Najah Islamic - Fauzan Prasetyo Eka Putra; Iksan; Nailus Saadah (Jurnal Informasi dan Teknologi, 2024)
The development of a web-based academic information system at Darun Najah Islamic Middle School is an important step in increasing the efficiency and effectiveness of academic data management. The Agile Scrum method is used as the main approach in this research to deal with the dynamics of changing user needs. This research describes the system development process which includes requirements analysis, design, development, testing and system implementation. The implementation results show a significant increase in flexibility, adaptability, and user involvement in the development of academic information systems. Additionally, implementing Agile Scrum also presents challenges related to adequate user involvement and accurate time and cost estimates. Implications for subsequent system development include the use of an iterative model and an emphasis on continuous delivery to ensure the system is relevant and adaptive to changing educational needs.